Lost in change causes and processes in the loss of grammatical elements and constructions - Kranich, Svenja; Breban, Tine, 1980- (Studies in language companion series,, 2021)
"While research on language change has formulated robust empirical generalisations about processes and motivations underlying the emergence and spread of linguistic elements, their decline and loss is less well understood. So far a systematic investigation into the processes and motivations of decline and loss in language change is lacking. This book is a first step towards remedying this state of affairs. It brings together a varied set of empirical investigations into decline and loss, spanning morphology, syntax and the lexicon, in different languages. Their authors apply diverse methodologies and represent different theoretical approaches. On the basis of this broad span of studies, authors and editors propose generalisations related to decline and loss and assess similarities and differences with processes and motivations of emergence and spread. The book aims to inspire and provide hypotheses for further studies of decline and loss. It will appeal to historical linguists and others interested in language change"--